2013
DOI: 10.6002/ect.2012.0098
|View full text |Cite
|
Sign up to set email alerts
|

Total Laparoscopic Donor Nephrectomy In Situs Inversus Totalis: A Case Report

Abstract: Situs inversus totalis is a rare anomaly characterized by the total inversion of all abdominal and thoracic organs. For the first time, we report a case of a donor nephrectomy in a patient with situs inversus totalis, completed with a full laparoscopic approach. At the time of this writing, the donor and the recipient are doing well after 6 month's follow-up. Our experience shows that patients with situs inversus totalis may be eligible candidates for laparoscopic donor nephrectomy, provided that detailed preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A right renal mass was incidentally found upon imaging. There are only three case reports of renal cell carcinoma concominant with situs inversus in literatüre (4,9,10). Our case is the first one in English language.…”
Section: Discussionmentioning
confidence: 72%
“…A right renal mass was incidentally found upon imaging. There are only three case reports of renal cell carcinoma concominant with situs inversus in literatüre (4,9,10). Our case is the first one in English language.…”
Section: Discussionmentioning
confidence: 72%
“…Most of the authors failed to indicate the duration of the donor and recipient follow-up period, except for two authors who reported follow-up periods of 6 and 12 months, respectively 31,32 . It may be observed that greater experience of surgeons leads to higher number of laparoscopic donor nephrectomies 29,31,32 . We reported a case of successful predialysis kidney transplantation from a donor with SIT without major associated blood vessel anomalies or associated syndromes appearing in 20-25% of SIT cases 8,33 .…”
Section: Discussionmentioning
confidence: 98%
“…Surgical approach may include open nephrectomy, hand-assisted laparoscopic donor nephrectomy and laparoscopic nephrectomy [29][30][31][32] . Most of the authors failed to indicate the duration of the donor and recipient follow-up period, except for two authors who reported follow-up periods of 6 and 12 months, respectively 31,32 . It may be observed that greater experience of surgeons leads to higher number of laparoscopic donor nephrectomies 29,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…There are some articles about laparoscopic donor nephrectomies with SIT [5,6]. The articles reported that SIT is not a barrier in performing these surgeries.…”
Section: Discussionmentioning
confidence: 99%